Decyzje strategiczne jako podstawa transgresji w przedsiębiorstwie - Jankowska-Mihułowicz, Marzena (Strategic Decisions as a Basis of Transgression in Company, 2008)
The conception of transgression and also the relationships between individual transgression and making strategic decisions in an enterprise are presented in this paper. Conditions in which strategic decisions are transgression decisions are defined. Additionally the role of transgression decisions for company management is explained.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 122-127